2014
DOI: 10.4136/ambi-agua.1263
|View full text |Cite
|
Sign up to set email alerts
|

Resíduos de pesticidas em sedimento de fundo de rio na Bacia Hidrográfica do Rio Cuiabá, Mato Grosso, Brasil

Abstract: The Cuiabá River is a major tributary of the Paraguay River; its basin is of great importance and encloses the Pantanal, the world's largest wetland. The economic base in the 84 Juliana Possavatz et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
(15 reference statements)
0
6
0
10
Order By: Relevance
“…The lake is located in a region where winter is characterized as a season with a lower rainfall. Rain directly interferes with the entry of water into the lake, interfering with the movement and sedimentation of particles contaminated by pesticides (Possavatz et al, 2014). Therefore, the average concentration of disulfoton in the winter was higher due to a lower water movement and higher sediment stability.…”
Section: Spatial and Temporal Analysis Of Pesticide Concentrationsmentioning
confidence: 99%
“…The lake is located in a region where winter is characterized as a season with a lower rainfall. Rain directly interferes with the entry of water into the lake, interfering with the movement and sedimentation of particles contaminated by pesticides (Possavatz et al, 2014). Therefore, the average concentration of disulfoton in the winter was higher due to a lower water movement and higher sediment stability.…”
Section: Spatial and Temporal Analysis Of Pesticide Concentrationsmentioning
confidence: 99%
“…Rio Cuiabá, Mato Grosso, evidenciando que há potencial para transporte de resíduos de agrotóxicos para dentro do ambiente aquático (POSSAVATZ et al, 2014). Carbendazim, diuron, imidacloprido, l-cialotrina, metomil e tebuconazol também já foram detectados em águas subterrâneas de outras regiões (CARBO et al, 2008;HERRERO-HERNÁNDEZ et al, 2013;PINHEIRO; …”
Section: Resultsunclassified
“…Em áreas de atividade agrí-cola, a principal preocupação é a contaminação dos recursos hídricos com resíduos de agrotóxicos, sendo que o principal mecanismo para avaliar o impacto do setor e promover políticas voltadas à saúde e o meio ambiente é o monitoramento da qualidade das águas (GAMA; OLIVEIRA; CAVALCANTE, 2013). Esse monitoramento pode ser realizado através de análises laboratoriais periódicas da água e/ou solo, em função dos agrotóxicos utilizados em uma determinada cultura (FILIZOLA et al, 2002;POSSAVATZ et al, 2014). No entanto, o fato de se tratar de áreas amplas, da grande quantidade e diversidade de agrotóxicos autorizados para cada cultura e do reduzido número de laboratórios de análise credenciados e de recursos humanos capacitados, o monitoramento da qualidade das águas pode não atender eficientemente às demandas de um país com dimensões continentais como o Brasil.…”
unclassified
See 1 more Smart Citation
“…Multiple studies have detected soy production insecticides in both sediment and water collected from streams in Argentina and Brazil; however, most studies did not include all of the most frequently used insecticides, and data were not always comparable because of the use of variable matrices, methods, and reporting limits (Jergentz et al 2004a;Mugni et al 2010;Di Marzio et al 2010;Marino and Ronco 2005;Possavatz et al 2014;Casara et al 2012;Miranda et al 2008;Laabs et al 2002). Several studies in Argentina and Brazil have found associations between stream insecticide concentrations and effects to aquatic invertebrates and/or fish (Jergentz et al 2004a;Rico et al 2010;Di Marzio et al 2010;Mugni et al 2010;Chelinho et al 2012); however, no studies of this type have been published on data collected from Paraguay.…”
Section: Introductionmentioning
confidence: 99%